THE ROLE OF M-PAYMENT QUALITY CHARACTERISTIC ON PERFORMANCE EXPECTATION AND SATISFACTION IN SURABAYA (STUDI OF MOBILE BANKING) - Kurniasari, Ardiana; Setiadi, Pompong (Review of Management and Entrepreneurship, 2023)
This study aims to determine the effect of M-payment quality characteristic on performance expectations and satisfaction of mobile banking users in Surabaya. This study uses quantitative methods and data from questionnaires distributed to 180 mobile banking users in Surabaya. The data was processed using SEM-PLS. The theoretical basis of this study is the information system success model (IS) with six dimensions: information quality, system quality, service quality performance expectation, usage intention, and user satisfaction. This study found that information quality, system quality, and service quality in mobile banking significantly affected performance expectations and user satisfaction of mobile banking users in Surabaya.